Uso del dise\~no de experimentos para la innovación empresarial; Use of experiments design for business innovation - Mercedes Delgado Fernández (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2020)
– The article deals with the use of experimental design in business innovation projects. Firstly, the foundations of experimental design are presented, with special emphasis on the process approach and its applicability in innovation. The second section proposes a guide for its application in business innovation projects, such as products, processes, organizational and marketing. The initial information for the application of the guide is based on the cause -effect diagram. Finally, three case studies of business innovation projects are presented in which the experiment design guide is applied, by means of which it is decided which factors are related to the causes that influence the response variable in correspondence with the analyzed ffect. In this way, the manager of the company would have more knowledge to make decisions that contribute to the increase of efficacy and efficiency.
Keywords: C4; C9; O3; 330; design of experiments; analysis of variance; cause-effect diagram; business innovation